Ivermectin and gemcitabine combination treatment induces apoptosis of pancreatic cancer cells via mitochondrial dysfunction - Lee, Da Eun; Kang, Hyeon Woong; Kim, So Yi; Kim, Myeong Jin; Jeong, Jae Woong; Hong, Woosol Chris; Fang, Sungsoon; Kim, Hyung Sun; Lee, Yun Sun; Kim, Hyo Jung; Park, Joon Seong (Frontiers in Pharmacology, 2022)
Pancreatic cancer is an aggressive cancer characterized by high mortality and poor prognosis, with a survival rate of less than five years in advanced stages. Ivermectin, an antiparasitic drug, exerts antitumor effects in various cancer types. This is the first study to evaluate the anticancer effects of the combination of ivermectin and gemcitabine in pancreatic cancer. We found that the ivermectin–gemcitabine combination treatment suppressed pancreatic cancer more effectively than gemcitabine alone treatment. The ivermectin–gemcitabine combination inhibited cell proliferation via G1 arrest of the cell cycle, as evidenced by the downregulation of cyclin D1 expression and the mammalian target of rapamycin (mTOR) /signal transducer and activator of transcription 3 (STAT-3) signaling pathway. Ivermectin–gemcitabine increased cell apoptosis by inducing mitochondrial dysfunction via the overproduction of reactive oxygen species and decreased the mitochondrial membrane potential. This combination treatment also decreased the oxygen consumption rate and inhibited mitophagy, which is important for cancer cell death. Moreover, in vivo experiments confirmed that the ivermectin–gemcitabine group had significantly suppressed tumor growth compared to the gemcitabine alone group. These results indicate that ivermectin exerts synergistic effects with gemcitabine, preventing pancreatic cancer progression, and could be a potential antitumor drug for the treatment of pancreatic cancer.